Building on Progress Expanding the Research Infrastructure for the Social, Economic, and Behavioral Sciences - Recommendations of the German Data Forum (RatSWD) (Verlag Barbara Budrich, 2011)
This publication provides a comprehensive compendium of the current state of Germany's research infrastructure in the social, economic, and behavioural sciences. In addition, the book presents detailed discussions of the current needs of empirical researchers in these fields as well as of opportunities for future development.